New analytical and numerical models of a solar coronal loop: I. Application to forced vertical kink oscillations - Murawski K.; Solov'ev A.; Kras̈kiewicz J.; Srivastava A.K. (My University, 2025)
Aims. We construct a new analytical model of a solar coronal loop that is embedded in a gravitationally stratified and magnetically confined atmosphere. On the basis of this analytical model, we devise a numerical model of solar coronal loops. We adopt this model to perform the numerical simulations of its vertical kink oscillations excited by an external driver. Methods. Our model of the solar atmosphere is constructed by adopting a realistic temperature distribution and specifying the curved magnetic field lines that constitute a coronal loop. This loop is described by 2D, ideal magnetohydrodynamic equations that are numerically solved by the FLASH code. Results. The vertical kink oscillations are excited by a periodic driver in the vertical component of velocity, which is acting at the top of the photosphere. For this forced driver with its amplitude 3 km s-1, the excited oscillations exhibit about 1.2 km s-1 amplitude in their velocity and the loop apex oscillates with an amplitude in displacement of about 100 km. Conclusions. The newly devised analytical model of the coronal loops is utilized for the numerical simulations of the vertical kink oscillations, which match well with the recent observations of decayless kink oscillations excited in solar loops. The model will have further implications on the study of waves and plasma dynamics in coronal loops, revealing physics of energy and mass transport mechanisms in the localized solar atmosphere. © ESO, 2015.